Genetics and Epigenetics of Spontaneous Intracerebral Hemorrhage - Giralt-Steinhauer, Eva; Jiménez-Balado, Joan; Fernández-Pérez, Isabel; Rey Álvarez, Lucía; Rodríguez-Campello, Ana; Ois, Ángel; Cuadrado-Godia, Elisa; Jiménez-Conde, Jordi; Roquer, Jaume (International journal of molecular sciences, 2022)
Intracerebral hemorrhage (ICH) is a complex and heterogeneous disease, and there is no effective treatment. Spontaneous ICH represents the final manifestation of different types of cerebral small vessel disease, usually categorized as: lobar (mostly related to cerebral amyloid angiopathy) and nonlobar (hypertension-related vasculopathy) ICH. Accurate phenotyping aims to reflect these biological differences in the underlying mechanisms and has been demonstrated to be crucial to the success of genetic studies in this field. This review summarizes how current knowledge on genetics and epigenetics of this devastating stroke subtype are contributing to improve the understanding of ICH pathophysiology and their potential role in developing therapeutic strategies.